RANCANG BANGUN SISTEM INFORMASI PENDETEKSI SUHU TUBUH MANUSIA DALAM PADEMIK COVID-19 - anto, ridy; ELISA, ERLIN (LPPM Universitas Putera Batam, 2021)
At this time, COVID-19 pandemic is a major problem in various parts of the world. Especially in Indonesia, this problem has spread to multiple regions. The government has taken various preventive measures, one of which is maintaining distance, washing hands, not crowding out. Preventative things have been done, but according to Google data that cases in Indonesia continue to increase every day. This is certainly not good. For this reason, researchers are eager to help the government and society the way to prevent this spread of the COVID-19 virus. Researchers plan to create tools and information systems that all groups can use to prevent this virus by using tools such as Raspberry Pi, Python, WEB, MLX90614, and others. with this, researchers hope to help in the prevention and spreading of the virus COVID-19.